Buckling of Carbon Honeycombs: A New Mechanism for Molecular Mass Transportation - Chengyuan Wang (The Journal of Physical Chemistry C, 2017)
Buckling of carbon honeycombs (CHCs) under uniaxial compression is studied based on molecular dynamics simulations. The uniaxial load applied to CHCs finally induces the local buckling associated with the biaxial compression state. This phenomenon originates from the residual stress in the CHCs due to the edge effect of component graphene nanoribbons. Under such a biaxial stress state, CHCs are found to exhibit two topographically different buckling modes when subjected to the uniaxial compression in the armchair and zigzag directions, respectively. In particular, the nonlocal effect originating from van der Waals interactions greatly reduces the ability of CHCs to resist structural instability and leads to early onset of CHC buckling. The buckling of CHCs is expected to be instrumental in the future applications of CHC structures. As an example, we show that an effective transportation of molecular mass enabled by the local buckling of CHCs is promising for the future CHC-based gas storage. In particular, the key issue to implement the transportation of the adsorbed gas molecules inside CHCs is to optimize the geometric size of CHCs in favor of the local buckling rather than the global buckling.